Study Of Social Skills And Their Relationship To Psychological Adjustment Among A Sample Of Basic Education Students With Hearing Disabilities (Damascus University Journal of educational and Psychologyical sciences, 2024)
This research aims at studying the correlation relationship between social skills and psychological compatibility, as well as to test the differences in social skills and psychological compatibility according to the variables of gender, the basic education cycle, the pupils’ grade, and the number of hearing disabilities in the family. To achieve these goals, the social skills scale prepared by Abu Manssour (2011), and the psychological compatibility scale prepared by Kabajeh (2011) were used. The sample consisted of (56) male and female students of basic education level with hearing disabilities. The concluded results are:• The level of social skills and psychological compatibility among the members of the research sample was at a medium degree.• There is a medium, positive correlation between social skills and psychological compatibility among the members of the research sample.‎• There are no statistically significant differences between the performance averages of the research sample members on the social skills scale according to the gender variable.‎• There are no statistically significant differences between the performance averages of the research sample members on the psychological compatibility scale according to the gender variable.• There are statistically significant differences between the performance averages of the research sample members on the social skills scale, according to the variable of the basic education cycle, in favor of the students of the second cycle.‎• There are statistically significant differences between the performance averages of the research sample members on the psychological compatibility scale according to the variable of the basic education cycle, in favor of the second round students.• There are statistically significant differences between the performance averages of the research sample members on the social skills scale and the psychological compatibility scale according to the academic grade variable, in favor of the eighth graders.• There are no statistically significant differences between the performance averages of the research sample members in social skills and psychological compatibility according to the number of hearing disabilities in the family variable.
Keywords: Social Skills, Psychological Compatibility, Hearing Impaired